2009
DOI: 10.1111/j.1474-9726.2008.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

The Human Ageing Genomic Resources: online databases and tools for biogerontologists

Abstract: SummaryAging is a complex, challenging phenomenon that requires multiple, interdisciplinary approaches to unravel its puzzles. To assist basic research on aging, we developed the Human Ageing Genomic Resources (HAGR). This work provides an overview of the databases and tools in HAGR and describes how the gerontology research community can employ them. Several recent changes and improvements to HAGR are also presented. The two centrepieces in HAGR are GenAge and AnAge. GenAge is a gene database featuring genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
174
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 34 publications
3
174
0
Order By: Relevance
“…Dozens of genes have now been associated with human longevity (de Magalhã es et al, 2009a), although only a handful of genes have been shown to have consistent effects across populations.…”
Section: A Functional Genomics Of Aging and Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dozens of genes have now been associated with human longevity (de Magalhã es et al, 2009a), although only a handful of genes have been shown to have consistent effects across populations.…”
Section: A Functional Genomics Of Aging and Longevitymentioning
confidence: 99%
“…Hundreds of genes that modulate longevity have now been identified in model organisms (de Magalhã es et al, 2009a). In some cases (e.g., in worms), mutations in single genes can extend lifespan by almost 10-fold (Ayyadevara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…After this scan, 15,312 proteins had at least one other ortholog. Aging-related proteins based on findings from model organisms were obtained from the GenAge database of de Magalhães et al (2009a).…”
Section: Data Retrieval and Ancestral Sequence Predictionmentioning
confidence: 99%
“…By comparing the two sets of genes, LAGs 20 and polarity-associated genes, 10 we selected eight candidates, with potential relevance to polar mRNA transport. The selected genes were reported to be involved in budding or mating processes, establishment of cell polarity and RNA binding ( Table 1).…”
Section: Discussionmentioning
confidence: 99%